Modeling PFAS Fate and Transport in Groundwater, with and Without Precursor Transformation. Issue 1 (7th December 2021) - Gefell, Michael J.; Huang, Hai; Opdyke, Dan; Gustafson, Kyle; Vlassopoulos, Dimitri; McCray, John E.; Best, Sam; Carey, Minna
Abstract: Groundwater professionals require tools to evaluate a variety of technical issues related to per‐ and polyfluoroalkyl substances (PFAS). These include the potential impact of PFAS precursors on groundwater plumes of perfluoroalkyl acids (PFAAs). Numerical modeling results show that, by adjusting the mass loading rate, source zones with or without a precursor can produce similar PFAA plumes. However, if a precursor is present, it can impact PFAA plume concentrations and extend PFAA plume durations by decades. Additional research regarding in situ precursor transformation rates—and improvements in source area characterization—will further advance the predictive value of modeling.